The Decibel Diaries : A Journey through Rock in 50 Concerts - Alan, Carter (Book collections on Project MUSE., 2017)
Carter Alan chronicles a lifetime in rock with a tour through fifty concerts in nearly fifty years of rock 'n' roll.